«Вечер мерцаний» [“The night оf glimmers”] - Sobolev, Alexander (Slavica Revalensia, 2019)
This is an extensively documented record of the aftermath of a failed poetic performance called “Vecher Mertsanii” (“The Night of Glimmers”). The performance took place in Moscow on December 19th, 1907, and its failure led to the shift in the policy of “Obshchestvo svobodnoi estetiki” (“The Society of Free Aesthetics”) from something that initially encouraged all forms of artistic experiment to something entirely subordinate to the vigilant leadership of one person exercising (if not exceeding) his authority – Valery Bryusov.